Pengaruh Digital Technology Advancement Dan Budaya Organisasi Terhadap Akuntabilitas Kinerja Instansi Dengan Lingkungan Kerja Sebagai Variabel Intervening Pada Kantor Dinas Perhubungan Provinsi Sumatera Barat - Zaky, Muhammad; Kumbara, Vicky Brama; Charli, Chintya Ones (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to determine the extent of the influence of Digital Technology Advancement and Organizational Culture on Agency Performance Accountability with the Work Environment as an Intervening Variable at the Transportation Agency of West Sumatra Province. This study uses a quantitative approach with a survey method on employees of the Transportation Agency of West Sumatra Province. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS. The sampling method in this study used a saturated sampling method by distributing questionnaires to 76 employees of the Transportation Agency of West Sumatra Province. The results of the study show that digital technology advancement has a positive effect on the work environment. In addition, digital technology advancement has a positive relationship with agency performance accountability. However, digital technology advancement has not been able to significantly mediate the relationship between the work environment and agency performance accountability even though its influence is positive.